Indoor tanning and skin cancer in Canada: A meta-analysis and attributable burden estimation. (April 2019) - O'Sullivan, Dylan E.; Brenner, Darren R.; Demers, Paul A.; Villeneuve, Paul J.; Friedenreich, Christine M.; King, Will D.; ,
Highlights: Over 10% of Canadian adults used an indoor tanning device in the past year and over a quarter had used an indoor tanning device in their lifetime. 7.0% of melanomas, 5.2% of basal cell carcinomas, and 7.5% of squamous cell carcinomas in Canada in 2015 were attributable to indoor tanning. The proportion of melanoma and non-melanoma skin cancer cases in Canada attributable to indoor tanning was greatest among young women. Abstract: Background: Consistent epidemiologic and experimental studies have demonstrated that UV-emitting tanning devices cause melanoma and non-melanoma skin cancer. The purpose of this study was to estimate the relative risk of skin cancer associated with the use of indoor tanning devices relevant to Canada, to estimate the proportion and number of skin cancers in Canada in 2015 that were attributable to indoor tanning, and to explore differences by age and sex. Methods: Skin cancer cases attributable to the use of an indoor tanning devices were estimated using Levin's population attributable risk (PAR) formula. Relative risks for skin cancer subtypes that were relevant to Canada were estimated through meta-analyses and prevalence of indoor tanning was estimated from the 2006 National Sun Survey. Age- and sex-specific melanoma data for 2015 were obtained from the Canadian Cancer Registry, while estimated NMSC incidence data were obtained from the 2015 Canadian Cancer Statistics report. Results: Ever use of indoor tanning devices was associated with relative risks of 1.38 (95% CI 1.22–1.58) for melanoma, 1.39 (1.10–1.76) for basal cell carcinoma (BCC), and 1.49 (1.23–1.80) for squamous cell carcinoma (SCC). Overall, 7.0% of melanomas, 5.2% of BCCs, and 7.5% of SCCs in 2015 were attributable to ever of indoor tanning devices. PARs were higher for women and decreased with age. Conclusion: Indoor tanning contributes to a considerable burden of skin cancer in Canada. Strategies aimed at reducing use should be increased and a total ban or restrictions on use and UV-intensity should be considered by health regulators.